Metabolism and secretory function of white adipose tissue: effect of dietary fat - Cláudia M. Oller do Nascimento; Eliane B. Ribeiro; Lila M. Oyama (Anais da Academia Brasileira de Ciências, 2009)
Approximately 40% of the total energy consumed by western populations is represented by lipids, most of them being ingested as triacylglycerols and phospholipids. The focus of this review is to analyze the effect of the type of dietary fat on white adipose tissue metabolism and secretory function, particularly on haptoglobin, TNF-α, plasminogen activator inhibitor-1 and adiponectin secretion. Previous studies have demonstrated that the duration of the exposure to the high-fat feeding, amount of fatty acid present in the diet and the type of fatty acid may or may not have a significant effect on adipose tissue metabolism. However, the long-term or short-term high fat diets, especially rich in saturated fatty acids, probably by activation of toll-like receptors, stimulated the expression of proinflammatory adipokines and inhibited adiponectin expression. Further studies are needed to investigate the cellular mechanisms by which dietary fatty acids affect white adipose tissue metabolism and secretory functions. Aproximadamente 40% do total de energia consumida pela população ocidental é representada pelos lipídios, a maioria dela sendo ingerida na forma de triglicerídeos e fosfolipídios. O foco desta revisão foi analisar o efeito dos tipos de gordura da dieta sobre o metabolismo e função secretora do tecido adiposo branco, principalmente, sobre a secreção de haptoglobina, TNF-α, inibidor do ativador de plasminogênio-1 e adiponectina. Estudos prévios demonstraram que durante a exposição de dietas hiperlipídicas, a quantidade e o tipo de ácidos graxos presentes na dieta podem ou não ter um efeito significante sobre o metabolismo do tecido adiposo. Entretanto, o tratamento a curto ou longo prazo com dieta hiperlipídica, especialmente rica em ácidos graxos saturados, provavelmente por ativar receptores toll-like, estimula a expressão de adipocinas pró-inflamatórias e inibe a expressão de adiponectina. Estudos adicionais são necessários para investigar os mecanismos celulares pelos quais os ácidos graxos da dieta afetam a função secretória e metabólica do tecido adiposo branco.